MATHEMATICAL MODEL TO INVESTIGATE THE DRAG REDUCTION OF KEROSENE WITH POLYMER UNDER TURBULENT FLOW (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
This paper present a mathematical study on drag reduction by polymer additive suchas poly isobutylene (PIB) with kerosene in turbulent pipe flow by using computational fluiddynamic commercial package program (COMSOL 4.4) solution. Theoretically thecomputational study was used to calculate the pressure drop in two dimensions geometricmodel with 6m length and 80 mm width as a diameter of the pipe, Geometric shape has beendrawing by tools of the program windows, and to simulated the flow region mathematicallythe flow region is divide into very small parts (mesh generation). The model that used in themathematical modelling method was (k-?( mathematical turbulent model to study theinternal pipe flow properties. The continuity and momentum equations and two k-? modelequations have been solved by the program to obtain the theoretical results. There variablesthat used in the theoretical study were effective density, effective viscosity, inlet velocity,and outlet pressure. The boundary condition was inlet and outlet velocity, temperature, andpressure of flow, and the velocity (u=0) at the pipe wall. The theoretical calculations showthat the velocity and drag reduction percentage increases with polymer concentration andvolume flow rate increasing where maximum DR% is 15.8% at volume flow rate 500 ??minwith polymer concentration 100 ppm, pressure drop decreases with polymer concentrationincreasing. Friction factor decreases with polymer concentration increased, also shear stressdecrease with polymer concentration increasing.